2022
DOI: 10.1002/iub.2611
|View full text |Cite
|
Sign up to set email alerts
|

Golgi quality control and autophagy

Abstract: Organelles can easily be disrupted by intracellular and extracellular factors. Studies on ER and mitochondria indicate that a wide range of responses are elicited upon organelle disruption. One response thought to be of particular importance is autophagy. Cells can target entire organelles into autophagosomes for removal. This wholesale nature makes autophagy a robust means for eliminating compromised organelles. Recently, it was demonstrated that the Golgi apparatus is a substrate of autophagy. On the other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…7 ). There exists a close relationship between GA fragmentation and autophagy ( 28 ). We demonstrated that autophagy was promoted during GA fragmentation whereas it was correspondingly suppressed when GA fragmentation was inhibited by overexpression of GRASP65 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 ). There exists a close relationship between GA fragmentation and autophagy ( 28 ). We demonstrated that autophagy was promoted during GA fragmentation whereas it was correspondingly suppressed when GA fragmentation was inhibited by overexpression of GRASP65 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Under certain physiological and pathological circumstances, GA disorganizes into membrane fragments and small vesicles and diffuses throughout the cytoplasm, namely, GA fragmentation ( 27 ). GA fragmentation has been revealed to be involved in autophagy ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fragmented ER and mitochondria need to be engulfed by autophagosomes. Meanwhile, Golgi fragmentation is broadly observed in both physiological and pathological conditions, in which the Golgi ribbon structure becomes unlinked/unstacked, and is dispersed throughout the cytoplasm as tubules/vesicles (Chang and Yang, 2022 ; Wei and Seemann, 2017 ). Golgi fragmentation is induced during mitosis, under various Golgi stresses, and in pathological conditions such as apoptosis, infection, amyotrophic lateral sclerosis, Alzheimer’s disease, Parkinson’s disease, and cancer (Chang and Yang, 2022 ; Wei and Seemann, 2017 ), in addition to starvation (Lu et al, 2020 ; Nthiga et al, 2021 ; Takahashi et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%